Reconstructive surgery of the upper lip using local rotation flap and secondary commissuroplasty after combined resection of the upper lip and buccal mucosa: A case report. Issue 5 (September 2022) - Takeshita, Akinori; Matsunaga, Kazuhide; Nojima, Satoshi; Kajikawa, Hitomi; Meshii, Noritoshi; Okumura, Masashi; Nishiyama, Kyoko; Kimura, Tomomasa; Morita, Yoshihiro; Suzuki, Mao; Uzawa, Narikazu
Abstract: Reconstructive surgery is essential for lip defect reconstruction, considering both lip form and function. We managed a patient who underwent upper lip reconstruction with a local flap after combined resection of the upper lip and buccal mucosa for salivary gland carcinoma. A 54-year-old, male patient had diffuse swelling with redness from the nasal base to the nasolabial groove and the upper white lip area on the right side. A 33 × 31 × 15 mm tumor was found extending from the upper right lip to the cheek. On imaging examination, enhanced computed tomography revealed an ill-defined heterogeneous mass with exophytic growth, and T2-weighted magnetic resonance imaging showed that the lesion showed heterogeneous high intensity. Histopathological examination of a biopsy specimen revealed clear cell carcinoma. As observed, more than one-third and less than half of the upper lip, including the commissure on the right side was resected. Therefore, through our ingenuity in shrinking the resected area, the skin and subcutaneous tissue above the nasolabial groove was triangulated and sutured. The Estlander flap of the lower lip on the affected side was selected for defect reconstruction. After surgery, the oral commissure on the affected side became drooping, thick, and round. Therefore, secondary commissuroplasty was performed 6 months postoperatively. One year after the secondary commissuroplasty, the morphology and function of the lips are almost satisfactory. Thus, we propose that combining the Estlander flap and secondary commissuroplasty helps reconstruct of less half of the upper lip.